2018
DOI: 10.1111/bdi.12625
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory processing in bipolar disorder, major depression, and anxiety

Abstract: Collectively, these findings indicate that odor identification difficulties may exist in mood disorders, especially when psychotic features are present. In contrast, the global olfactory dysfunction observed in schizophrenia may not be a feature of other neuropsychiatric conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
58
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 58 publications
(80 reference statements)
6
58
1
1
Order By: Relevance
“…Pathway analysis incorporating all nominally-significant microarray hits (including those with low differential expression) suggested that 667-Coumate may perturb olfactory transduction processes and that this perturbation may mediate drug-induced effects on postpartum maternal behaviour in the mouse; potentially, the increased prevalence of postpartum mood disorder in STS deficient women may be partially attributable to abnormalities within the olfactory system and/or its links to the limbic system. This possibility is feasible in light of the clinical observation that 667-Coumate administration can elicit taste disturbances in female patients [Stanway et al, 2006], and is consistent with an extensive literature on the importance of olfactory (and associated limbic) function in mammalian mothers [Corona and Levy, 2015], with evidence that several steroid sulfates act as ligands within the mouse accessory olfactory system [Meeks et al, 2010], with the expression of multiple olfactory receptors within human brain tissue [Flegel et al, 2013], and with recent findings that olfactory processes are perturbed in a genetic mouse model of abnormal maternal behaviour [Creeth et al, 2018] and multiple mood disorders [Kamath et al, 2018].…”
Section: Discussionsupporting
confidence: 82%
“…Pathway analysis incorporating all nominally-significant microarray hits (including those with low differential expression) suggested that 667-Coumate may perturb olfactory transduction processes and that this perturbation may mediate drug-induced effects on postpartum maternal behaviour in the mouse; potentially, the increased prevalence of postpartum mood disorder in STS deficient women may be partially attributable to abnormalities within the olfactory system and/or its links to the limbic system. This possibility is feasible in light of the clinical observation that 667-Coumate administration can elicit taste disturbances in female patients [Stanway et al, 2006], and is consistent with an extensive literature on the importance of olfactory (and associated limbic) function in mammalian mothers [Corona and Levy, 2015], with evidence that several steroid sulfates act as ligands within the mouse accessory olfactory system [Meeks et al, 2010], with the expression of multiple olfactory receptors within human brain tissue [Flegel et al, 2013], and with recent findings that olfactory processes are perturbed in a genetic mouse model of abnormal maternal behaviour [Creeth et al, 2018] and multiple mood disorders [Kamath et al, 2018].…”
Section: Discussionsupporting
confidence: 82%
“…The CSIT made up for the shortage of olfactory evaluation based on the Chinese population. Some experts suggested that the subjects were just the patients with MDD in previous studies, and then reached the conclusion that the lower odor identification performance belongs to these individuals with MDD 33,34 . However, mild or moderate depression do not accompany with olfactory dysfunction 7 .…”
Section: Discussionmentioning
confidence: 99%
“…These data are all the more relevant given the small number of studies published to date, and the contradictory results these studies have reported. Nonetheless, the study by Kamath et al warrants further consideration.…”
mentioning
confidence: 92%
“…A recent issue of Bipolar Disorders featured a paper by Kamath et al in which they compared olfactory performance in patients with bipolar disorder, major depression, and anxiety to that in (non‐mood disorder) controls. In this paper, Kamath et al showed that individuals with major depression and bipolar disorder (with psychotic features) had poorer odor identification compared to controls, and that those with major depression demonstrated reduced accuracy in recognizing neutral odors. The authors concluded that alterations in odor identification may exist in mood disorders, particularly in bipolar patients with psychotic features, and that these disturbances are less marked than those reported for schizophrenia in which olfactory dysfunction is more global.…”
mentioning
confidence: 99%
See 1 more Smart Citation